Allocation of Expenditure of Poor Family as a Recipient of Program Keluarga Harapan (PKH) - Rizkillah, Risda; Simanjuntak, Megawati (Journal of Family Sciences, 2018)
The aim of this article is to examine the allocation of expenditure for low-income families after receiving the Program Keluarga Harapan (PKH) or Conditional Cash Transfer (CCT). Combination of cross-sectional and retrospective designs were applied in this research. Data collection locations were carried out in eight villages in Dramaga District, Bogor Regency. The research sample was determined randomly (probability sampling) used a systematic method and obtained a study sample of 150 CCT recipient families. Data was processing used descriptive statistics. The CCT funding eligible for the family who has school-age children, toddlers, nursing mother, and pregnant woman. The CCT funds are spent by families with an average range of two weeks. The beneficiary of PKH significantly improving the quality of education and health, increasing the amount of family savings, and family income. The allocation of CCT funds more than half is used for human investment. However, in the allocation of CCT funds, there are still families who use PKH funds for non-educational activities such as food/household needs, pay-off debt, saving, electricity payment, and business capital.